Family metro maps - Jan Korst; Verus Pronk; Jarke J. van Wijk (Journal of Visualization, 2022)
We present family metro maps as a new approach to visualize the relations between multiple related families. A family is represented by a metro line, where the parents are the end nodes and the children the intermediate nodes. We introduce family trees as rooted binary trees and consider the problem of automatically drawing a family metro map for a given family tree without crossing line segments, where the successive nodes of a metro line are placed at equal distances. The inter-node distance may be chosen to depend on the generation of the family, such that metro lines of earlier generations are shown more prominently than metro lines of later generations. Family metro maps can be used to visualize the family relations of the descendants of multiple couples that have common descendants.